The ethics of the New Finance - Horrigan, James O. (Journal of business ethics, 1987)
This paper examines the normative ideas flowing from the contemporary theories that make up the New Finance. These theories include the Irrelevance Theorem, Efficient Market Hypothesis, Capital Asset Pricing Model, Options Pricing Model, and Agency Theory. The behavioral consequences that would ensue if everyone took the normative precepts of the New Finance seriously are subjected to a Kantian analysis to determine their ethical implications. It is concluded that the corporate world in the New Finance is a place where the firm can select any operating and financial strategies that it wishes, and the investors will respond immediately through a combination of homemade portfolio diversification, clever option positions, and carefully constructed agency relationships, all of which results in a pervasive nihilism. Recommendations are offered on how these features of the New Finance might be avoided or moderated.